2022
DOI: 10.3390/ijerph19169959
|View full text |Cite
|
Sign up to set email alerts
|

Designing Mobile Epidemic Prevention Medical Stations for the COVID-19 Pandemic and International Medical Aid

Abstract: The demand for mobile epidemic prevention medical stations originated from the rapid spread of the COVID-19 pandemic. In order to reduce the infection risk of medical practitioners and provide flexible medical facilities in response to the variable needs of the pandemic, this research aimed to design mobile medical stations for COVID-19 epidemic prevention, the emergence of which began in February 2020. The mobile medical stations include a negative pressure isolation ward, a positive pressure swabbing station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A study in Nepal suggested that community health worker-collected mobile phone data as a possible adjunct to surveillance for diarrhea in a resource-limited setting ( 14 ). Taiwan developed a mobile medical station for the immediate treatment and screening of covid affected individuals ( 43 ). We collaborated with the DGHS in Bangladesh to implement a rule-based AI COVID-19 digital surveillance platform for community mobilization in urban and rural areas, involving over 13,700 community clinics, 138 urban primary healthcare centers, and over 30,000 government and non-government health workers or social volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Nepal suggested that community health worker-collected mobile phone data as a possible adjunct to surveillance for diarrhea in a resource-limited setting ( 14 ). Taiwan developed a mobile medical station for the immediate treatment and screening of covid affected individuals ( 43 ). We collaborated with the DGHS in Bangladesh to implement a rule-based AI COVID-19 digital surveillance platform for community mobilization in urban and rural areas, involving over 13,700 community clinics, 138 urban primary healthcare centers, and over 30,000 government and non-government health workers or social volunteers.…”
Section: Discussionmentioning
confidence: 99%